Efficacy and safety of salvage radiotherapy combined with endocrine therapy in patients with biochemical recurrence after radical prostatectomy: A systematic review and meta-analysis of randomized controlled trials - Liang, Zhanpeng; Lin, Sihong; Lai, Huiqin; Li, Luzhen; Wu, Jiaming; Zhang, Huatang; Fang, Cantu (Frontiers in Oncology, 2023)
Background The addition of endocrine therapy to salvage radiotherapy (SRT) is expected to further improve the prognosis of patients with biochemical recurrence of prostate cancer after radical prostatectomy (RP). The quantitative synthesis of clinical outcomes of SRT combined with endocrine therapy is limited. Whether salvage radiotherapy plus endocrine therapy remains inconclusive. We performed a systematic review and meta-analysis of existing randomized controlled trials to evaluate the efficacy and safety of salvage radiotherapy combined with endocrine therapy in patients with biochemical recurrence after radical prostatectomy. Methods A systematic search of PubMed, EMBASE, and the Cochrane library was performed for articles published between January 1, 2012 and October 10, 2022. Data were analyzed using Review Manager 5.4.1 (Cochrane Collaboration Software). Main outcome and measures included biochemical progression-free survival (bPFS), metastasis free survival (MFS), overall survival (OS), and Grade 3 or higher adverse events (3+AEs), including acute and late adverse events. Results In this systematic review and meta-analysis, 4 randomized controlled studies enrolling 2731 male (1374 of whom received SRT combined with endocrine therapy and 1357 controls) met the inclusion criteria. SRT combined with endocrine therapy were related to significantly improve bPFS (HR=0.52; 95% CI: 0.46 0.59; p<0.00001) and MFS (HR=0.75; 95% CI: 0.64 0.88; p<0.001). Compared with SRT alone, the combination therapy tended to be associated with prolong OS (HR=0.83; 95% CI: 0.69-1.01; p=0.06), but not statistically significant. At early follow-up, the risk of acute AEs was comparable in the two groups (RR=1.04; 95% CI: 0.22-4.85). However, the risk of late AEs was higher in the combination group at later follow-up (RR=1.33; 95% CI: 1.09-1.62). Conclusions This systematic review and meta-analysis found superior efficacy associated with adding endocrine therapy to SRT compared with SRT alone in patients with biochemical recurrence after RP. Additional endocrine therapy is safe and feasible for patients with biochemical recurrence after RP. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier (CRD42022365432).